2014
DOI: 10.1073/pnas.1405723111
|View full text |Cite
|
Sign up to set email alerts
|

Contact inhibition and high cell density deactivate the mammalian target of rapamycin pathway, thus suppressing the senescence program

Abstract: Significance This work solves longstanding mysteries in the field of contact inhibition (CI), cancer, and aging. As shown here during CI, cells do not undergo senescence, thus resuming proliferation after replating. We found that CI was associated with inhibition of the mammalian target of rapamycin (mTOR) pathway, which is required for the senescence program. In cancer cells, lacking CI, mTOR was still inhibited in high cell density by an alternative mechanism. Our work explains why CI is reversible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
121
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 54 publications
14
121
0
Order By: Relevance
“…The presence of an additional product of the INK4a/b locus, with higher capacity to induce cellcycle arrest, may confer an added protection to naked mole rat cells, contributing to cancer resistance of this species. It was recently shown that contact inhibition represses mTOR and thus suppresses the senescence program (44). Thus, it is tempting to speculate that ECI in naked mole rats mediated by the unusual structure of the INK4a/b locus may contribute to naked mole rat longevity, in addition to conferring cancer resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an additional product of the INK4a/b locus, with higher capacity to induce cellcycle arrest, may confer an added protection to naked mole rat cells, contributing to cancer resistance of this species. It was recently shown that contact inhibition represses mTOR and thus suppresses the senescence program (44). Thus, it is tempting to speculate that ECI in naked mole rats mediated by the unusual structure of the INK4a/b locus may contribute to naked mole rat longevity, in addition to conferring cancer resistance.…”
Section: Discussionmentioning
confidence: 99%
“…13,[19][20][21][26][27][28][29][30][31][32][33][34] Senescence is an irreversible, proliferationinhibiting response that occurs in 2 steps: 1) reversible cell cycle arrest followed by 2) futile growth-induced gerogenic conversion, or geroconversion. [35][36][37] Moreover, senescence is a major tumorsuppressive mechanism that acts as an early barrier to thwart cancer development. The presence of senescent cells in benign lesions, but not advanced malignant tumors, suggests that senescence barriers must be dismantled during oncogenic progression.…”
Section: Introductionmentioning
confidence: 99%
“…When cell cycle is arrested, the growth signal (if it cannot reactivate cycling) drives senescence. It was shown that inhibition of mTOR precludes senescence (by inhibiting the so called geroconversion) and causes reversible quiescence [26][27][28][29] . These data are in accord with our previous observation that isolated breast cancer cells, residually left behind after surgery and Temsirolimus treatment in mice, are quiescent for a certain time and eventually re-grow, resulting in tumor recurrence [9].…”
Section: Discussionmentioning
confidence: 99%